2020
DOI: 10.1038/s41598-020-73398-1
|View full text |Cite
|
Sign up to set email alerts
|

Exudation of organic acid anions by tropical grasses in response to low phosphorus availability

Abstract: It has been suggested that some tropical grasses can acquire phosphorus (P) from hematite and gypsite by exuding organic acid anions (OAs). However, it remains to be determined exactly which OAs could be involved in each case. The objective of this study was to verify the exudation OAs by ruzigrass (Urochloa ruziziensis), palisade grass (U. brizantha), and Guinea grass (Megathyrsus maximus) as a response to P deficiency. The grasses were grown in leachate columns with adequate and deficient P nutrient solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…Another uncertainty in assessing the actual importance of microbes in soil K solubilization is the survival of these microorganisms in unfavorable environments [50]. However, organic acid exudates may have had a considerable effect in the present experiment, since ruzigrass roots have been shown to release significant amounts of organic acids such as citrate, isocitrate, and oxalate [53]. Therefore, we infer that the ruzigrass DM yields without K fertilizer were, proportionally, less affected by successive crops than those of maize and soybean (Figure 1B) due to exudation of organic acids that promoted soil K release.…”
Section: Discussionmentioning
confidence: 82%
“…Another uncertainty in assessing the actual importance of microbes in soil K solubilization is the survival of these microorganisms in unfavorable environments [50]. However, organic acid exudates may have had a considerable effect in the present experiment, since ruzigrass roots have been shown to release significant amounts of organic acids such as citrate, isocitrate, and oxalate [53]. Therefore, we infer that the ruzigrass DM yields without K fertilizer were, proportionally, less affected by successive crops than those of maize and soybean (Figure 1B) due to exudation of organic acids that promoted soil K release.…”
Section: Discussionmentioning
confidence: 82%
“…The accumulation of OAs, such as citramalate, citrate, α‐ketoglutarate, malate, malonate, succinate and isocitrate, increased in the roots but not in the leaves (with the exception α‐ketoglutarate whose level increased) of chickpea plants in response to Pi deficiency (Figures 4, 7 and S8; Table S1). The exudation of these OAs, which could contribute to Pi‐solubilization, into the rhizosphere and apoplastic spaces of the roots is a highly effective strategy for improving Pi acquisition efficiency (Almeida et al., 2020; Pant et al., 2015; Pueyo et al., 2021). Interestingly, pyruvate, which is the end‐product of glycolysis and is involved in adjusting the flow of glycolytic metabolites into the TCA cycle (Fataftah et al., 2018), showed decreased levels in the roots of chickpea plants under Pi deficiency (Figures 4 and S8; Table S1), suggesting that it might have been transformed to acetyl‐CoA at a higher rate under such stress conditions for entering into the TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
“…For Ca-P forms, a remarkable change was observed in the concentration and proportion of available Ca 2 -P increased under marsh degradation, whereas those of unavailable Ca 10 -P decreased (Figures 3a-d and 4a-b). This is because marsh desiccation accompanied by the transition of the plant community or overgrazing may enhance the activity and/or quantity of phosphate-dissolving bacteria, such as Pseudomonas , Bacillus, and Erwini (Liu et al, 2015;Susilowati et al, 2019) and increase the organic acids from plants, microbes, and/or livestock excreta (Almeida et al, 2020;Gyaneshwar et al, 2002;Miao et al, 2013;Nuryana et al, 2019). Improved phosphate-dissolving bacteria and organic acids can further stimulate the transformation of Ca 10 -P to other labile inorganic P forms such as Ca 2 -P, Ca 8 -P, and Al-P (Almeida et al, 2020;Susilowati et al, 2019).…”
Section: Marsh Degradation Influences the Transformation Of Soil Phos...mentioning
confidence: 99%
“…This is because marsh desiccation accompanied by the transition of the plant community or overgrazing may enhance the activity and/or quantity of phosphate-dissolving bacteria, such as Pseudomonas , Bacillus, and Erwini (Liu et al, 2015;Susilowati et al, 2019) and increase the organic acids from plants, microbes, and/or livestock excreta (Almeida et al, 2020;Gyaneshwar et al, 2002;Miao et al, 2013;Nuryana et al, 2019). Improved phosphate-dissolving bacteria and organic acids can further stimulate the transformation of Ca 10 -P to other labile inorganic P forms such as Ca 2 -P, Ca 8 -P, and Al-P (Almeida et al, 2020;Susilowati et al, 2019). Similarly, Jamil et al (2016) revealed that Calcisols with greater biological activity under sugarcane crop cover had a high concentration of Ca 2 -P in the estuary plains of Pakistan.…”
Section: Marsh Degradation Influences the Transformation Of Soil Phos...mentioning
confidence: 99%
See 1 more Smart Citation